Characterizing cognitive aging of recognition memory and related processes in animal models and in humans - Barnes, Carol A.; Burke, Sara N.; Ryan, L. (Frontiers in Aging Neuroscience, 2012)
Analyses of complex behaviors across the lifespan of animals can reveal the brain regions that are impacted by the normal aging process, thereby, elucidating potential therapeutic targets. Recent data from rats, monkeys and humans converge, all indicating that recognition memory and complex visual perception are impaired in advanced age. These cognitive processes are also disrupted in animals with lesions of the perirhinal cortex, indicating that the the functional integrity of this structure is disrupted in old age. This current review summarizes these data, and highlights current methodologies for assessing perirhinal cortex-dependent behaviors across the lifespan.